TINJAUAN PENGEMBANGAN MATERIAL BERBASIS BARIUM TITANAT, KOMPOSIT PVDF/BATIO3 DAN BATIO3/HAP UNTUK APLIKASI ELECTROSTATIC DIELECTRIC ENERGY STORAGE CAPACITOR - Septian Rahmat Adnan; Budhy Kurniawan; Bambang Soegijono (Jurnal Rekayasa Mesin, 2023)
Barium titanate (BaTiO3) is ceramic material that is widely used in various applications..Electrostatic dielectric energy storage capacitor is one of the application of Barium titanate (BaTiO3) material. Composite materials based on barium titanate (BaTiO3) such as Polyvinylidene fluoride (PVDF)/BaTiO3 and BaTiO3/HAp Hydroxyapatite have been developed to improve the electrical properties of the materials. Many research have been reported hat barium titanate in nano phase has a maximum dielectric constant 5000 with particle size range of 30-50 nm. The addition of BaTiO3 composition as a filler to PVDF/BaTiO3 composite caused increasing of dielectric constant compared to the dielectric constant properties of the PVDF. Similar results also found on BaTiO3/HAp composite. From this review, it was also found that the composite of these three materials is a candidate for future material to improve the electrical properties of PVDF which have been applied to electrostatic dielectric energy storage capacitor applications.